The mind of the criminal: the role of developmental social cognition in criminal defense law - Fontaine, Reid Griffith (Cambridge University Press, 2012)
"This book discusses the excusing nature of both traditional and nontraditional criminal law defenses and questions the structure of these defenses based on scientific findings from social and developmental psychology"--